Population crunch in India: is it urban or still rural? - Sudhira, H. S.; Gururaja, K. V. (Current science (Bangalore), 2012)
The article attempts to present analysis based on the provisional results of the Census 2011. While there is no doubt that the human social organization of the country is undergoing a transition, the nature of growth however is subject to the lens through which this is viewed. Noting the dichotomy of urban and rural definitions, we question the rationality of the 'urban' definition and its relevance.